Uniform NaLuF4 nanoparticles with strong upconversion luminescence for background-free imaging of plant cells and ultralow power detecting of trace organic dyes. (January 2016) - Hu, Shigang; Wu, Xiaofeng; Chen, Zenghui; Hu, Pan; Yan, Huanyuan; Tang, Zhijun; Xi, Zaifang; Liu, Yunxin
Graphical abstract: Based on the efficient luminescence resonant energy transfer (LRET) can be observed from upconversion naonparticles (UCNPs) to dyes, an excitation power limit of 60 μW can be achieved in detecting traces of RB in plant cells. Highlights: Upconversion nanoparticles with strong visible luminescence are successfully synthesized. Luminescence resonance energy transfer (LRET) can be observed from UCNPs to dyes. Based on LRET, an excitation power limit of 60 μW can be achieved in detecting traces of dye. Abstract: Yb 3+ and Er 3+ /Tm 3+ co-doped NaLuF4 upconversion nanoparticles (UCNPs) with strong visible luminescence under the excitation of infrared light are successfully synthesized. The synthesized NaLuF4 upconversion nanorystals have acidic ligand and can quickly capture the basic dyes to form UCNPs@dye nanosystem, in which the efficient luminescence resonance energy transfer (LRET) can be observed from UCNPs to dyes. We select NaLuF4 :Yb 3+ /Er 3+ UCNPs as a model to detect Rhodamine B (RB) in plant cells. NaLuF4 :Yb 3+ /Er 3+ UCNPs can emit green light at the wavelength of ∼545 nm while RB can efficiently absorb the green light of ∼545 nm to emit red light of 610 nm. As a result, the LRET process can occur in NaLuF4 :Yb 3+ /Er 3+ @RB system. Based on the LRET process, an excitation power limit of 60 μW can be achieved in detecting traces of RB in plant cells. This LRET process is also used for detecting sodium fluorescein with the excitation power limit of 65 μW.